HUBUNGAN PERLEMAKAN HATI DENGAN GAMBARAN HISTOPATOLOGI PASIEN ADENOKARSINOMA KOLON DI RUMAH SAKIT KANKER DHARMAIS TAHUN 2018-2019 - Goldy Natanael (2022)
Background: Colon cancer is one of the most frequent cancers worldwide. In 2020, colon cancer contributes to 6% of all cancers in the world. Non-alcoholic fatty liver disease (NAFLD) is a liver disease that happens in 30% of the Indonesian population. Previous studies have suggested that NAFLD may be a risk factor for colon cancer and that there was a high prevalence of colon cancer patients with NAFLD. This study aimed to determine the prevalence of fatty liver in colon adenocarcinoma patients in Indonesia and its associations with their differentiation grade and invasion depth. Methods: This study was a retrospective cross-sectional study conducted in Dharmais Cancer Hospital, Jakarta, Indonesia. Patients who had colon adenocarcinoma confirmed by histopathology from 2018-2019 were studied from their medical records to obtain their anthropometric measures, ALT, AST, differentiation grade, and depth of invasion of the adenocarcinoma. Patients' liver was assessed with Hepatic Steatosis Index (HSI) scoring. The data obtained was then computed statistically with the chi-square test or Kolmogorov Smirnov test. Results: 84 patients were included in the study. It was found that 14.3% of the patients have fatty liver. Bivariate analysis showed that HSI groups and well-differentiated and moderate-poor-differentiated adenocarcinoma have the p-value of 0,026. The p-value of HSI groups and invasion depth of the adenocarcinoma was 1. Conclusion: The prevalence of fatty liver in patients with colon adenocarcinoma was 14.3%. There was an association between fatty liver and differentiation grades. There was no association between fatty liver and invasion depth.